Public attitudes toward traditional Chinese medicine and how they affect medical treatment choices in Hong Kong. Issue 2 (13th June 2018) - Chan, Kara; Tsang, Lennon
Abstract : Purpose: This study aims to test a conceptual model using public attitudes toward biomedicine and traditional Chinese medicine (TCM) to predict respondents' medical treatment choice. Design/methodology/approach: A quantitative online survey was conducted using quota sampling. Altogether 1, 321 questionnaires from Hong Kong residents of age 15 years or above were collected. Findings: Attitudes toward biomedicine in relation to TCM and perceived cost of TCM consultation were found to be significant variables in predicting respondents' medical treatment choice of treatment. Perceived efficacy of TCM, however, was not a significant predictor. Older respondents, as well as respondents with higher education, were less likely to consult biomedicine first when ill. They were also less likely to consult biomedicine exclusively. Research limitations/implications: This study uses a convenience sample recruited through personal networks. The findings cannot be generalized to the rest of the population. Practical implications: Respondents in the study generally perceived TCM's efficacy to be high, but not high enough to make it the medical treatment of choice. To promote TCM in Hong Kong, there is a need to enhance trust in it. This can be achieved through strengthening scientific research and development of TCM, enhancing professional standards of TCM practitioners and educating the public about the qualifications of TCM practitioners. Strategic channel planning to reach potential target and reducing the time cost of TCM medication should be examined. Originality/value: The study is the first to relate attitudes to and perceptions of TCM with medical treatment choices in Hong Kong.